Intracerebral interleukin-10 injection modulates post-ischemic neuroinflammation: An experimental microarray study - Liesz, Arthur; Bauer, Andrea; Hoheisel, Jörg D.; Veltkamp, Roland (Neuroscience letters, 2014)
Stroke induces a profound neuroinflammatory reaction that leads to secondary cerebral tissue injury. Interleukin-10 (IL-10) is a key anti-inflammatory cytokine that is endogenously produced by immune cells and limits this inflammatory reaction. Previously, therapeutic administration of IL-10 has been shown to be neuroprotective in experimental stroke. However, the signaling pathways affected by this approach are largely unknown. The aim of this study was to verify the neuroprotective effects of IL-10 in an experimental mouse stroke model and to analyze the pathways modulated by this approach. Therefore, we performed a whole genome microarray analysis comparing the cerebral gene expression profile at two time points after cortical stroke in IL-10-treated and control C57Bl/6J mice. We administered IL-10 locally by intracerebroventricular injection. We were able to validate a reduction of infarct volume by IL-10 administration and characterized the kinetics of endogenous cerebral IL-10 expression after stroke. The microarray analysis revealed that IL-10 treatment effectively downregulated pro-inflammatory signaling cascades which were upregulated by the ischemic lesion in the acute phase after the stroke. This is the first study characterizing the global gene regulation profile of IL-10 immunotherapy for ischemic stroke. Our results emphasize the key role of IL-10 as a neuroprotective cytokine and suggest several novel downstream pathways for further investigation to better understand the mechanisms of post-stroke neuroinflammation.